Rosliza Ibrahim v Kerajaan Negeri Selangor & Anor [2021] 3 CLJ 301 - Ali Mohamed, Ashgar Ali (CLJ Malaysia Sdn. Bhd., 2025)
The Syariah Court may only exercise jurisdiction over a person when it has over him both jurisdiction ratione personae, which is contingent on the person's legal persona, and jurisdiction ratione materia or subject matter jurisdiction. Absence these jurisdictions, the Syariah Court is not empowered to exercise any power over a person and if exercised would be ultra vires the Federal Constitution. This commentary basically reviewed the decision of the Federal Court in Rosliza's case with the view the author on the said decision.